Feasibility analysis of fishing business using floating bagan at batu belubang fish farm, Central Bangka - Dareen Nadya Rema; Zerli Selvika; Indah Citra Islamiyah; Gilang Putra Amuria; Afrilio Perdyansyah (Jurnal Perikanan Terpadu, 2026)
Batu Belubang Village plays a strategic role in the fisheries sector, with the floating lift net (bagan apung) as the main fishing gear, yet this sector continuously faces major challenges, notably catch fluctuations and rising operational costs. Within the framework of sustainable fisheries business, financial feasibility analysis serves as a fundamental theoretical basis for assessing business efficiency and resilience. Given the lack of comprehensive financial studies in this area, this research aims to analyze the financial feasibility of the floating lift net business through the indicators of profit (????), Rasio Penerimaan terhadap Biaya (R/C), Payback Period (PP) and Return on Investment (ROI). Understanding these metrics is crucial for providing strategic insight to fishermen and the government in managing resources for sustainable welfare.The analysis results show a business profit of Rp 8.283.963.333-,with an R/C value of 63.72, indicating that every rupiah of cost generates 63.72 times the revenue. The measured Payback Period is only 0.069 years or approximately 25 days, signifying a rapid return on capital. The ROI value, reaching 14.29%, confirms the financial feasibility of the floating lift net business, but this low figure indicates operational inefficiency and vulnerability to market fluctuations. Therefore, strategic interventions focused on processed product development, digital market expansion, and cost efficiency optimization are necessary to increase the ROI and ensure the business’s sustained profitability.